Design of Smart Door Lock as A Teaching Aid for Magnetic Field Material in High School - Emiliyanti, Rantika; Dedy Hamdani; Iwan Setiawan (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This research aims to 1) produce a product in the form of a smart door lock teaching aid based on the RFID RC522 sensor and Arduino Uno as a teaching aid for magnetic field material in high school, 2) determine the suitability of the teaching aid that has been created and developed, and 3) to determine students’ responses to props developed. This type of research is research and development (Research and Development, R&D), by applying the ADDIE development model, namely Analysis, Design, Development, Implementation, Evaluation. The tool that has been developed is then validated by three validators using an expert validation sheet instrument. The assessment of the product being developed consists of aspects of tool efficiency, tool relationship with learning, educational value, tool durability, aesthetics, technical and safety. The results of expert validation obtained an average validation percentage value of 80.55% with a very feasible category. Student responses to teaching aids were measured using a student response questionnaire. The results of student responses obtained an average response percentage of 84.19% in the good category. It can be concluded that the smart door lock based on the RFID RC522 sensor and Arduino Uno as a teaching tool for magnetic field topic can be used in studying magnetic fields in high school.